Testing Website Game Point Blank Menggunakan Metode Blackbox: Penelitian - Asgar Maulana; Eki Muhammad Heris; Laksamana Raihan N; Saobandri, Ridwan; Rizqia Noerlidha; Subhanjaya Angga Atmaja (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to evaluate the usability and functionality of the Point Blank ID website using black-box testing methodology. The website serves as a platform for gamers, providing essential information about the game, including promotions, items, and updates. The testing process involves assessing various aspects, including user navigation, information availability, functionality, responsiveness, and page load speed. The testing results indicate that while the website offers a wealth of information, several areas require improvement. Navigation is generally intuitive; however, some links were found to be non-functional, hindering the user experience. Additionally, the website's responsiveness varies across different devices, with noticeable issues on mobile platforms. The page load speed is fairly satisfactory, but delays were observed when accessing certain content, particularly images.